THE ROLE OF JAWI TAFSIR IN SOCIO-CULTURAL TRANSFORMATION OF THENUSANTARA ISLAM: A STUDY ONTARJUMĀNAL-MUSTAFĪD - Putra, D. I. Ansusa; Zikwan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
Studieson Islam in Nusantara are primarily related to Islam's transmission to Nusantara. Meanwhile, the role of vernacularization (localizing) of Islamic sciences by Nusantara scholars -including attention to vernacularization of interpretive science -gained less attention. This paper employs the vernacular concept from A.H. Johns, discussing the role of Jawi Tafsir in the Islamization of Nusantara in the early phases of both the formulation of Islamic Nusantara Islam and the socio-cultural transformation of Nusantara. The conceptual frameworks are related to enculturation, adoption, and cultural adaptation, in which vernacularization occurs in each of these processes. Through studies on the Jawi's vernacular interpretation (Tarjumān al-Mustafīd), this paper argues that in the early scientific formulation of the Nusantara Islam that transformed the socio-cultural Nusantara, Tarjumān al-Mustafīd played a significant role. With another Jawi commentaries, Tarjumān al-Mustafīd then became the Nusantara's Islamic identity and proof of Islam with the archipelago's character.